Spectroscopic and Thermal Properties for Exploding Silver Wire Plasma in Deionized Water - Moaen, Fatimah Jumaah; Humud, Hammad R. (Iraqi Journal of Science, 2022)
The goal of this research is to use optical emission spectroscopy to investigate the parameters of exploding silver wire plasma. The silver discharge plasma's emission spectra were recorded and studied. For silver wire of diameter 0.4 mm and different currents 75,100, and 125A in deionized water, the plasma electron temperature ( ) was calculated by Boltzmann plot and container plasma medium temperature by thermal camera, and the electron density ( ) was computed by Stark broadening using the hydrogen (H line) at 656.279 nm With increasing current from 75 to 125 A, the electron density (ne) increased from 3.160×  to 8.762×   , while electron temperatures increased from 0.571 to 1.334 eV under the same conditions.  The plasma's optical emission spectrum (OES) includes a peak at 653 nm that corresponds to the H line of the hydrogen atom, as well as additional peaks that belong to Ag (AgI and AgII lines). Researchers looked into the relationship between plasma electron temperature, emission line intensity, and number density. Nanoparticle concentration rises as the intensity of the emission line rises, while their size decreases. It is feasible to deduce that plasma parameters have a regulated relationship with the concentration and size of nanoparticles produced.